Mitigação da reação álcali-agregado em concreto com o emprego de resíduo de cerâmica vermelha e metacaulim - Cachepa, Moisés Mário (Universidade do Vale do Rio dos Sinos, 2017)
The use of mineral additions through pozzolans, both naturally and artificially, has been adopted by several civil engineering professionals through the partial substitution of cement primarily in the production of concrete slabs, with the aim of improving some of the characteristics such as: Reduction of the heat of hydration, improvement of the workability, increase of the resistance to compressive strength, increase of the durability in aggressive environments, reduction of the emission of CO2, reduction of the appearance of efflorescence and reduction of the expansions due to the alkali-aggregate reactions. One of the pathologies that greatly affects mass concrete structures such as dams is the alkali-aggregate reaction, which is understood to be a chemical process occurring in concrete, in which some mineralogical constituents present in the aggregate react with hydroxides from the cement that are dissolved In the solution of the pores forming an expansive hygroscopic gel. The elaboration of this work, on the one hand, was motivated by the fact that one of the main dams in Africa located in Mozambique, shows signs of expansion according to several authors and, on the other hand, as a way of evaluating the Pozolan potential of RCV and MK. This work aimed to evaluate the mitigation of the alkali-aggregate reaction in concrete through the use of residues of red ceramics and metakaolin as pozzolans. The RCV was purchased as a waste from the production of ceramic blocks, while the MK was from a commercial product. In order to reach the objective, the RCV and MK underwent an investigation taking into account physical, chemical, mineralogical characteristics and the determination of the index of the pozzolanic activity. Both RCV and MK had pozzolanic activity index higher than the 90% established by NBR 12653 (2014). The aggregate used was classified as potentially reactive through analyzes of petrography, DRX, FRX and accelerated method of mortar bars. For the evaluation of RAA, samples were prepared and analyzes of aggregate reactivity and mineral additions efficiency were performed using the accelerated method of mortar bars, compressive strength and water capillary absorption in a substitution of 20% and 30% of cement by RCV, MK and RCV + MK, in the following curing ages: 48h, 28 days in Ca (OH) 2 and 28 days of immersion in NaOH solution. By the expansion results, it was possible to verify that all materials and cement substitution contents by pozzolans proposed had a reduction of less than 0.10% recommended by ASTM C1567 (2013), classified as insufficient to cause deleterious reactions due to potential Pozolânico of the MK and RCV. It was possible to verify that the higher the alkaline equivalent, the larger the expansions, the smaller the Ca / Si ratio, the smaller the expansions, the higher the alumina content, the smaller the expansions, the smaller the average equivalent size Of the particles, the smaller the expansions, and the larger the total porosity, the larger the expansions. The results of the compressive strength and water absorption showed that the mixtures submitted to the accelerated test presented worse performance in relation to the cured mixtures in Ca (OH) 2 due to the microstructure of the mortars, creating internal microcracks, or because the formed gel permeable to water penetration.
Keywords: Reação álcali-agregado; Resíduos de cerâmica vermelha; Metacaulim; Pozolana; Material cimentício suplementar; Alkali-aggregate reaction (RAA); Red ceramic residues (RCV); Metakaolin (MC); Cement; Pozolana; Aggregate; Concrete; ACCNPQ::Engenharias::Engenharia Civil